Long-term patient-reported knee-related outcomes and quality of life of patients with tibial plateau fractures: A mixed-methods study - Nynke van der Gaast; Britt H. J. Edwards; Dagmar S. Alderlieste; Ruurd L. Jaarsma; Job N. Doornberg; Michael J. R. Edwards; Erik Hermans (PLOS One, 2026)
Objective This study aims to provide a comprehensive assessment of the long-term functional outcomes in patients who sustained a tibial plateau fracture by combining patient-reported outcomes and a qualitative analysis of their healthcare experiences and compare the long-term outcomes of tibial plateau fracture patients with a matched healthy population. Methods Patients who were treated for a tibial plateau fracture at an Australian trauma-center, were asked to complete two questionnaires. The outcomes of our patient sample were compared to those of a matched sample of the general population. Lastly, in-depth interviews were conducted in a subset of participating patients to gain insight in their treatment experiences. Results Among 165 eligible patients treated at an Australian trauma center for a tibial plateau fracture, 46 participated in the study, with 18 patients consenting to in-depth interviews. Patients who sustained a tibial plateau fracture exhibited significant worse outcomes compared to a matched healthy population. Their quality of life were significantly lower for patients with tibial plateau fractures compared to a matched health population. The qualitative analysis highlights patient perspectives and suggests potential improvements, such as standard referral to physical therapy and optimization of support services. Conclusion This study demonstrates the substantial impact of tibial plateau fractures on knee-related outcomes and quality of life for patients, 5–10 years post-injury. The qualitative findings of this study revealed that patients wished to improve the implementation of physical therapy and improving support services to potentially achieve optimal healthcare.